Molecular analysis of hemaglutinin gene of Avian Influenza viruses isolated in 2012-2013 - Kurniasih, Sussi Widi; Soejoedono, Retno D.; Mayasari, N.L.P.I. (Indonesian Journal of Animal and Veterinary Sciences, 2015)
Avian Influenza virus (AIV) still plays as a major cause of the death in poultry in Indonesia and around the world. The aim of this research was to determine the pathogenicity and to analyze the phylogenetic and genetic distances of hemagglutinin gene of isolated AI viruses in Indonesia in 2012-2013 particularly from West Java, Central Java, and North Sumatra. Samples were obtained from poultry farms that suffered from AI outbreaks, were inoculated and propagated in ten days old specific pathogen free (SPF) embryonated chicken eggs. Harvested allantoic fluids at 5 days after inoculation were tested for hemagglutination activity. Positive allantoic fluids were further tested to determine the hemagglutinin and neuraminidase subtype using real-time reverse transcription polymerase chain reaction (RRT-PCR) and to be prepared for sequencing using reverse transcription polymerase chain reaction (RT-PCR). The sequence of hemagglutinin genes were analyzed for the amino acid pattern of the cleavage site region and the genetic distances and relationships of those viruses. The result indicated that all of the isolates are classified as HPAI with the pattern of cleavage site regions are QRESRRKKR and QRERRRKR. Six isolates are classified as H5N1 and 3 isolates are H5Nx. All of the isolates have close genetic relationship with the genetic distances less than 0.3 between one to another and also with several AI viruses that caused previous outbreaks in Indonesia. Key Words: Avian Influenza, Cleavage Site, Hemagglutinin, Pathogenicity, Phylogenetic